Slaughter Characteristics of Feedlot-Finished Premium South African Lamb: Effects of Sex and Breed Type - Daniël André Van der Merwe; Tertius Swanepoel Brand; Louwrens Christiaan Hoffman (Foods, 2020)
This study compared the carcass characteristics of ram and ewe lambs from South African wool, dual-purpose, meat, and fat-tailed sheep types, reared to produce premium lamb carcasses. The lambs were reared on a feedlot diet (10.41 MJ ME/kg feed and 19.06% crude protein) from weaning (30 kg live weight) until they attained a back-fat depth of ~4 mm, measured using ultrasound. After slaughter, the carcasses were assessed for retail cut yields, composition, and physical meat quality. Later, maturing lambs attained heavier carcass weights than early maturing breeds (~20.7 kg vs. 16.9 kg, respectively; p ≤ 0.05), and differences in carcass composition and retail cut yields were ascribed to differences in the frame size and pattern of fat deposition of the respective breeds. Small differences in physical meat quality were observed, with meat from Dormer and Namaqua lambs having notably higher shear-force values (~46 N) than that from Meatmaster carcasses (~34 N). These differences though are expected to have little influence on the perceived quality of the meat.